Administrator Bezpieczeństwa Informacji a Inspektor Ochrony Danych na tle regulacji krajowych i unijnych — wybrane zagadnienia - Wygoda, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The main aim of this article is the attempt to conduct acomparative analysis of selected issues from the relationship between ABI Data Protection Officer/IOD Data Protection Inspecor and ADO Controller. The test area includes mainly issues related to the establishment of inspection bodies. In particular, this problem when it depends on the discretion of the ADO and in which cases turns into alegal obligation. The description includes the conditions set for the candidate for the ABI/IOD, and the process of their verification. Apart from main considerations the article provides also comments on the nature of the relationship between them and the ADO.
Keywords: Inspektor Ochrony Danych; Administrator Bezpieczeństwa Informacji; prawo polskie; prawo UE